Completion of the Verbs to Stand and Sit in Phraseological Units - Chopuryan, Gayane (Bulletin of Yerevan University B: Philology, 2022)
The study of the possibilities of completing the neuter antonym verbs to the Armenian verbs to stand and sit shows that these verbs require additional additions of place, form and size. In one case, the latter are expressed by morphemes and conjunctions, and in the other, by an invariable part of speech. Some additions expressed by morphemes have pairs expressed by other morphemes present in the dialect layer of the Armenian language. The phrases formed by the verbs in question are either colloquial or have a colloquial variant. The verb to sit is endowed with wider connective possibilities, which in some sentences has a double gender - connect and cross, thanks to conjunctive verbs, expresses the grammatical meaning of the passive gender, requiring the complement of the gender.